Productividad saludable - Saucedo, Vicente (2018)
As indicated by different studies, eating habits and work productivity can be related to each other. These habits prevent different types of diseases. Labour stress, for example can reduce the worker’s ability to analyse his environment objectively; and it can generate eating disorders, which can further reduce labour productivity. In fact, this relationship is also found within the human body through neurotransmitter dynamics. This essay highlights the importance of nutrition in labour output, as well as, in the worker ́s well-being.